(untitled) (Al-Qamar, 2021)
Addiction is an enemy of human senses, natural and mental capabilities; it has been the responsibility of a healthy society to protect human health and also to rehabilitate human intellect and its senses. That’s why drug addiction is considered as a thing of aversion in the evolutionary stages of human society. Presently the word is occupied with litigation for obviation of drugs addiction. In order to counteract drugs addiction, the study of all the collateral efforts made in this regard are utmost essential for Anti Norcotic Force so that it may be well aware of the definition of addiction and its kinds. Why because having no basic knowledge of drugs addiction progress and this field will not be in easy one. In this discourse besides modern dictions, the effort of religious scholars of Muslim Umma have been encompassed. The holy prophet (PBUH) has defined addiction very comprehensively and precisely-a unique one. As Imams Arbaa have mentioned the comprehensive and prohibitive problems of intoxication, they have also presented the definitions of intoxication before him. A list of ancient and modern addictions is provided so that readers can find additional information and a chapter on how to avoid them.